BOOKKEEPING TRAINING AND SELLING PRICE DETERMINATION FOR SMALL BUSINESSES IN GIRIAN ATAS VILLAGE - Pingkan Lonto, Miryam; Sumampouw, Olviane (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Bookkeeping is one of the important things done by every business actor, but it is often ignored by small business actors, especially those in Girian Atas Village. This happens because small business actors do not understand how to make bookkeeping, have not applied the concept of business entities, do not know how to calculate selling prices in accordance with cost accounting theory. Based on this reality, it is necessary to conduct training activities on Bookkeeping and Determination of Selling Price in Small and Medium Enterprises in Girian Atas Village. The activity was carried out in two stages. First, conduct training on bookkeeping and determination of cost of goods sold and selling price. Second, conducting evaluation and monitoring, to see the extent of the results of financial records of SMEs. The results of this activity have an impact on increasing knowledge and understanding of accounting and determining selling prices. Business actors have also been able to make simple financial statements, namely income statements, statements of changes in capital, and balance sheets. This is a good thing, because they can fulfill one of the requirements to apply for a credit loan at the bank, which will certainly help increase the capital of their business.